2014
DOI: 10.4304/jltr.5.5.994-998
|View full text |Cite
|
Sign up to set email alerts
|

Independent Study Logs: Guiding and Encouraging Students in the Process of Language Learning

Abstract: Abstract-Many people in Spain are studying English in order to find jobs in this country or to migrate as a result of the economic crisis. Language classes, however, are limited in duration and are often not enough to enable students to progress as much as they would like to. Language learners have to spend a considerable amount of time out of class studying and using English in order to get the most out of their class and to continue learning when classes are not in session. This article explains the use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition to facilitating and assessing language learning, in the EFL context, a log assignment is essentially used as a medium to promote autonomous learning. According to Litzler (2014), in writing logs, learners write information and reflections on various aspects of their learning, such as their reactions to a lesson and the methodology used, out-of-class activities carried out to learn English, and other aspects of the learning experience related to a specific language course. Lee and Cha (2017) found that the use of listening logs for extensive listening in a self-regulated environment not only developed learner autonomy among participants, but yielded learners' growth in their ability to summarize, express feelings, and improve English proficiency.…”
Section: Log Assignment As An Autonomous Learning and Assessment Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to facilitating and assessing language learning, in the EFL context, a log assignment is essentially used as a medium to promote autonomous learning. According to Litzler (2014), in writing logs, learners write information and reflections on various aspects of their learning, such as their reactions to a lesson and the methodology used, out-of-class activities carried out to learn English, and other aspects of the learning experience related to a specific language course. Lee and Cha (2017) found that the use of listening logs for extensive listening in a self-regulated environment not only developed learner autonomy among participants, but yielded learners' growth in their ability to summarize, express feelings, and improve English proficiency.…”
Section: Log Assignment As An Autonomous Learning and Assessment Toolmentioning
confidence: 99%
“…The results showed that students were generally positive about the learning logs as it helped them increase autonomy while working with English outside class, created self-awareness about learning strategies, and equipped them with new ways of learning a language. Litzler (2014) concluded that a log assignment is worth implementing in foreign language classes because students have a positive view of learning logs and it makes a significant contribution to the development of learners' autonomy.…”
Section: Log Assignment As An Autonomous Learning and Assessment Toolmentioning
confidence: 99%